First Report of a Population of Western Blacknose Dace (Rhinichthys obtusus) in the Brushy Creek System of the Black Warrior River Drainage, Alabama - Eric Bauer; Malorie M Hayes (Southeastern Fishes Council Proceedings, 2017)
Alabama is home to the southernmost populations of Rhinichthys obtusus, the Western Blacknose Dace. Within Alabama, R. obtusus is found in the Tennessee, Coosa, and Black Warrior River basins, but its presence in the Black Warrior River drainage has been limited. Until now, R. obtusus in the Black Warrior drainage has only been reported as collections of 1 to 4 specimens at a time in the Sipsey Fork drainage. Herein, we report two novel occurrences of R. obtusus in the headwaters of the Brushy Creek system in the Black Warrior River drainage including a singleton and a large population. The population observed in Collier Creek is located over 21 km from the Tennessee River divide, on the divide between the Brushy Creek system and the Sipsey Fork drainage, and is in close proximity to an artificial lake, any of which may be the origin of this population. The presence of a population of R. obtusus in the system necessitates further sampling of the headwaters of the Black Warrior River drainage to understand its natural prevalence in the region.
Keywords: Freshwater; Fish; Distribution; New occurrence